ANALISIS RESIKO PADA BAGIAN PRODUKSI PABRIK PENGOLAH GETAH KARET MENGGUNAKAN METODE HIRARC (Studi Kasus PT X Kota Padang) - Tivany Edwin; Rinda Andhita Regia; Mohammad Irfan; Yogi Kurniawan (Jurnal Sains dan Teknologi, 2019)
PT X is a company engaged in processing rubber gum into crumb rubber. Several incidents of work accidents are stillfound in the factory's production activities. For this reason, it is important to identify hazards, risk and determine thetype of risk control in the production section that is often found in the occurrence of PT X work accidents, by using theHIRARC Method. Risk analysis is done by multiplying the probability and severity of the occurrence of hazards in theprocessing of raw materials, drying blankets and processing of blankets on the dryer. The results showed that there foundno high risk level in the process. Low process level was found in the transfer process with forklft, the rest of activity werein the moderate risk level. The recommended controls are engineering, administrative controls and the use of personalprotective equipment.